Pemberdayaan Suami Dalam Kelas Hamil Pro Untuk Meningkatkan Kesehatan Ibu Dan Keharmonisan Rumah Tangga - Islah Wahyuni; Siti Maemaunah; Zesika Intan Novelia (Universitas Madako Tolitoli, 2025)
Pregnancy is a transformative period that demands comprehensive support for the mother. The role of the husband as the main support system is often overlooked in conventional pregnancy class programs. This community service activity aims to implement and evaluate the “Pregnancy Class Pro Husband Support” to improve maternal health and household harmony at the Kualu Kampar Midwife Clinic. The implementation methods included interactive workshops, practical simulations, and group discussions involving 25 couples of pregnant women and husbands. Data were collected through pre-test and post-test questionnaires to measure knowledge improvement, as well as questionnaires on perceived husband support and household harmony. Results showed a significant increase in knowledge scores of mothers (from fair 48% to good 84%) and husbands (from fair 52% to good 80%), an increase in perceived husband support (from negative 56% to positive 84%), and an increase in perceived household harmony (from negative 60% to positive 80%). The program proved effective in empowering husbands to be actively involved, which was positively correlated with maternal health and family dynamics. Recommendations include integrating the model into Puskesmas and PMB programs and developing further materials.